COGNITIVE AND METACOGNITIVE READING STRATEGY USE AND READING COMPREHENSION PERFORMANCE OF INDONESIAN EFL PRE-SERVICE TEACHERS - Sari, Mariska Intan (Journal of Foreign Language Teaching and Learning, 2016)
AbstractThe study aims at identifying the nature of cognitive and metacognitive reading strategies employed by Indonesian EFL pre-service teachers and the relationship on their reading comprehension, revealing whether the highly, moderately, and less successful EFL pre-service teachers differ in terms of reading strategies they employ in comprehending English texts and analyzing whether the differences in the use of these reading strategies relate to their performances in a reading comprehension test. The study employs a quantitative research method using reading test and cognitive and metacognitive reading strategy questionnaire. The results of the study show that there is no significant relationship between the cognitive and metacognitive reading strategies employed by Indonesian EFL pre-service teacher and their performance in a reading comprehension test. The results also show that there is no difference in the use of cognitive and metacognitive reading strategies between the less, moderately, and highly successful readers.            Keywords: cognitive strategies, metacognitive strategies, reading comprehensio